Management of Deep Carious Lesions (Springer International Publishing, 2018)
This book describes the challenges that deep carious lesions pose for dental practitioners, including the risk of endodontic complications and the difficulty of restorative treatment, and identifies options for overcoming these challenges on the basis of the best available evidence. The opening chapter sets the scene by discussing pathophysiology, histopathology, clinical symptomatology, and treatment thresholds. The various treatment options are then systematically presented and reviewed, covering non-selective, stepwise, and selective carious tissue removal and restoration, sealing of lesions using resin sealants or crowns, and non-restorative management approaches. In each case the current evidence with respect to the treatment is carefully evaluated. Advantages and disadvantages are explained and recommendations made on when to use the treatment in question. Illustrative clinical cases and treatment pathways for clinicians are included. This book will be of value for all practitioners who treat dental caries and carious lesions, whether in the permanent or the primary dentition. It will also be of interest to under- and postgraduate students in cariology and restorative, operative, preventive, and pediatric dentistry.